Fuzzy Logic Control Design in Hybrid Energy Storage System Super-Capacitor Battery for Electric Vehicle - Dhia, Thomi; Mardiyah, Nur Alif; Nurhadi, Nurhadi (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2019)
HESS is a suitable technology when applied to electric cars. One application is in SUV (Sport Utility Vehicle) car. The use of Supercapacitors can reduce the excess of load on the battery. Uneven soil contours cause current spike and drop in battery voltage which can reduce battery lifetime. This journal presents a simulated study of HESS batteries and Supercapacitors in SUV cars. Fuzzy-based energy management strategies and threshold control are introduced. The simulation study shows the difference between the control using the number of climb data and not, and the Fuzzy control response to the demand load. The simulation results mention the reduction of the maximum current and the battery voltage drop according to the load. The total energy ratio used between the two controls is also presented.